English Language Teaching at the University of Milan - Andrea Nava; Luciana Pedrazzini; Emanuela Tenca (Iperstoria)
Language teaching in Italian universities traditionally played second fiddle to the teaching of literature until the end of the 20th century. However, a number of English language and literature academics in different Italian universities were also authors of English language textbooks aimed at university and secondary school students, adults, and teachers. At the University of Milan, between the 1960s and 1980s, Esther Menascè combined her interest in literary research with the development of English language teaching materials addressed to different types of learners: university students, self-study learners, and secondary school students. This paper aims to investigate how Menascè’s interest in linguistics and foreign language teaching methodology led her to design innovative materials to respond to the needs of Italian learners and teachers at a time of reform and change at all educational levels. The content analysis of the teaching materials sampled shows Menascè’s interest in conducting applied research into English language teaching. This is reflected in the scientific description of English, especially as regards phonetics and phonology, as well as in her principled adoption first of techniques belonging to an aural-oral approach in her books published in the 1960s and 1970s, and then to communicative language teaching in the 1980s. These are innovative aspects in Menascè’s materials production which make her stand out as an academic and a textbook author in the Italian context of her time.